Spatial scale and duration of one microburst region on 13 August 2015. Issue 6 (1st June 2017) - Anderson, B. R.; Shekhar, S.; Millan, R. M.; Crew, A. B.; Spence, H. E.; Klumpar, D. M.; Blake, J. B.; O'Brien, T. P.; Turner, D. L.
Abstract: Prior studies of microburst precipitation have largely relied on estimates of the spatial scale and temporal duration of the microburst region in order to determine the radiation belt loss rate of relativistic electrons. These estimates have often relied on the statistical distribution of microburst events. However, few studies have directly observed the spatial and temporal evolution of a single microburst event. In this study, we combine Balloon Array for Radiation belt Relativistic Electron Losses balloon‐borne X‐ray measurements with Focused Investigations of Relativistic Electron Burst: Intensity, Range, and Dynamics II and AeroCube‐6 CubeSat electron measurements to determine the spatial and temporal evolution of a microburst region in the morning MLT sector on 13 August 2015. The microburst region is found to extend across at least 4 h in local time in the morning sector, from 09:00 to 13:00 MLT, and from L of 5 out to 10. The microburst event lasts for nearly 9 h. Smaller scale structure is investigated using the dual AeroCube‐6 CubeSats, and is found to be consistent with the spatial size of whistler mode chorus wave observations near the equatorial plane. Plain Language Summary: Microbursts are very short (quarter of a second) bursts of electron radiation occurring in the highest levels of Earth's atmosphere. The causes of microbursts are as yet unproven. This study carefully analyzes the spatial location and temporal evolution of microbursts in a new and novel way, utilizing data from satellites as well as balloon‐based measurements. Our findings help to establish a correlation between this important Space Physics phenomenon and possible causes that exist in Earth's Magnetosphere. Key Points: Balloon and CubeSat data constrain the spatial extent and temporal evolution of a microburst region The 13 August 2015 microburst event lasted for nearly 9 h beginning at 06:15 UT The 13 August 2015 microburst region extended from MLT of 09:00 to 13:00 and from L of 5 to 10